# Need Help Simplify Math Equation?

Completely simplify each expression

### 2 Answers

Relevance

- davidLv 77 days agoFavorite Answer
a. 4b^3c^2(-2bc^2)^3

= 4b^3c^2(-8b^3c^6)

= -32b^6c^8

b. [(3x^2y^2)/(4x^4y)]^-2

= (4x^4y)^2 / (3x^2y^2)^2

= (16x^8y^2) / (9x^4y^4)

= (16x^4) / (9y^2)

- Login to reply the answers

- sepiaLv 77 days ago
(a)

4b^3 c^2 (-2bc^2)^3

= 4b^3 c^2 (-8b^3c^6)

= -32 b^6 c^8

(b)

[(3x^2y^2)/(4x^4 y)^-2]

= [(3x^2y^2(4x^4 y)^2]

= [(3x^2y^2(16x^8 y^2)]

= 48x^10y^4

- Login to reply the answers

Still have questions? Get your answers by asking now.